ANALISIS PENGARUH BUDAYA ORGANISASI, KEADILAN ORGANISASI, DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Studi Pada PT Kereta Api Indonesia (Persero) Daerah Operasi 4 Semarang) - Maysarah, Sari; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
The development of public transportation in the field of railways in addition to the emphasis on quality and services to customers as a step fostering consumer trust also requires the management of human resources in order to obtain good quality human resources. The purpose of the research are to analysis how the influence of Organizational Culture, Organizational Justice, and Organizational Commitment on Organizational Citizenship Behavior (OCB) in PT Kereta Api Indonesia (Persero) Operating Area 4 Semarang.The Population used in this research were permanent employees of PT Kereta Api Indonesia (Persero) Operating Area 4 Semarang numbering 65 people. The sampling technique was conducted by using simple random sampling method. The analytical method used is multiple regression analysis. Research result of the regression equation is as follows: OCB = 0,182X1 + 0,488X2 +0,633X3Based on the test instrument, the indicators are valid and reliable. In the classical assumption, there are no symptoms multicoloniarity, does not occur heterocedastity, and normal distribution of data. The coefficient of determination shows the figure of 0,703 which means that the variables of Organizational Citizenship Behavior is influenced by variables of Organizational Culture, Organizational Justice, and Organizational Commitment amounting to 70,3%. The results showed that the Organizational Culture, Organizational Justice, and Organizational Commitment has positive and significant impact to Organizational Citizenship Behavior of PT Kereta Api Indonesia (Persero) Operating Area 4 Semarang partially as well as simultaneously.